GAMELAND: DESAIN PENGEMBANGAN PERTUNJUKAN KARAWITAN BERBASIS VIRTUAL DIGITAL ONLINE METAVERSE SEBAGAI UPAYA PEMAJUAN KEBUDAYAAN - Fajar Abed Nego; Denis Setiaji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2022)
Karawitan performing arts is one of the branches of art in Indonesia. The performing arts, which are based on music, still exist are carried out by art activists or karawitan artists. Karawitan is also one of the performing arts that has the potential to develop to the global scene. On the other hand, technology is growing rapidly, forcing everyone to continue to innovate in order to keep up with the world's technological currents. Gameland is one of the innovations sparked for the development of karawitan shows. Although it is still a design, it will be very possible to implement it in the future. The research conducted for Gameland design used descriptive quality methods. By using virtual metaverse technology, this design is expected to be able to be a medium for developing karawitan performances, improving the economy of artists, and promoting culture. Through Gameland's digital technology, artists can play and perform karawitan performances anywhere, anytime, and with anyone without being limited by space and time. Gameland exists as an effort to adapt to the progress of the era so that karawitan artists can continue to exist and develop with seamless connectivity relationships through the virtual world, the metaverse.